2010
DOI: 10.1007/s10528-010-9335-2
|View full text |Cite
|
Sign up to set email alerts
|

Insertion/Deletion Polymorphism and Serum Activity of the Angiotensin-Converting Enzyme in Turkish Patients with Obstructive Sleep Apnea Syndrome

Abstract: This study determined the allelic frequency and genotypic distribution of an angiotensin-converting enzyme (ACE) polymorphism and serum ACE activity in Turkish patients with obstructive sleep apnea syndrome (OSAS). A colorimetric assay measured serum ACE activity in 73 of 97 subjects. Frequencies for II, ID, and DD genotypes were 19.6, 53.6, and 26.8% in the OSAS group and 15, 38, and 47% in the control group, respectively (P = 0.02). The I allele frequency was higher in the OSAS group than in the healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Ogus et al (2010) found that ACE activity was significantly lower in severe than in mild OSAS. However, genotype differences do not exist between mild/moderate OSAHS and severe OSAHS in Ogus et al (2010) and 4 other studies in our meta-analysis.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Ogus et al (2010) found that ACE activity was significantly lower in severe than in mild OSAS. However, genotype differences do not exist between mild/moderate OSAHS and severe OSAHS in Ogus et al (2010) and 4 other studies in our meta-analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Based on our search strategy, the primary screening produced 21 potentially relevant articles, of which 15 met the inclusion criteria as an attempt to evaluate the association between the ACE I/D polymorphism and occurrence of OSAHS (Xiao et al, 1999;Zhang et al, 2000;Barcelo et al, 2001;Ping et al, 2001;Li et al, 2004a,b;Lin et al, 2004;Zhang et al, 2004;Gu et al, 2006;Li et al, 2006;Bostrom et al, 2007;Benjamin et al, 2008;Koyama et al, 2009;Ogus et al, 2010;Yakut et al, 2010). A total of 1361 OSAHS patients and 1373 controls were analyzed.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies [24,25] related angiotensin-converting enzyme (ACE) and IRS-1 gene polymorphisms [26], in related to sleep apne risk in Turkish patients with OSAS. Besides, IRS gene polymorphisms were investigated in glucose metabolism disorders [27,28].…”
Section: Medicine Science 2013;2(4):830-41 Irs Gene Polymorphism In Omentioning
confidence: 99%